8th International Congress on Mathematical Education : Selected Lectures - International Congress on Mathematical Education (8th : 1996 : Sevilla, Spain); Alsina, Claudi, editor 238256; Álvarez, José María, editor 653631; Hodgson, Bernard, editor 653632; Laborde, Colette, editor 653633; Pérez, Antonio, editor 653634 ([Seville, Spain] : S.A.E.M. Thales)
Includes bibliographical references.